When and Why Being Ostracized Affects Veracity Judgments. (March 2020) - Eck, Jennifer; Schoel, Christiane; Reinhard, Marc-André; Greifeneder, Rainer
Ostracism—being ignored and excluded by others—is a ubiquitous experience with adverse effects on well-being. To prevent further exclusion and regain belonging, ostracized individuals are well advised to identify affiliation partners who are sincerely well-disposed. Humans' ability to detect lies, however, is generally not very high. Yet, veracity judgments can become more accurate with decreasing reliance on common stereotypic beliefs about the nonverbal behavior of liars and truth-tellers. We hypothesize that ostracized (vs. included) individuals base their veracity judgments less on such stereotypical nonverbal cues if message content is affiliation-relevant. In line with this hypothesis, Experiment 1 shows that ostracized (vs. included) individuals are better at discriminating affiliation-relevant lies from truths. Experiments 2 and 3 further show that ostracized (vs. included) individuals base their veracity judgments less on stereotypical nonverbal cues if messages are of high (but not low) affiliation relevance.